(untitled) (American Journal of Islam and Society, 2018)
Muslim-American adolescents face unique developmental challenges, due to the national and global negative spotlight on Islam, as they navigate identity formation in the mainstream American setting. However, the intersection of various social identities (SI) in the navigation of these challenges has been ignored in much social-scientific literature. We examined the SI of Muslim-American adolescents using the multidimensional cluster analysis technique. Correlates of adolescents’ SI were also explored, specifically adolescents’ self-reported psychological well-being. One hundred and fifty Muslim adolescents were recruited from schools, mosques, and community organizations throughout Maryland. Follow-up analyses indicated that the High-Muslim/High-American adolescents reported the highest well-being and Moderate-Muslim/Undifferentiated-American cluster reported poorer well-being than the other clusters. Findings highlighted the importance of simultaneously assessing Muslim and American SIs, and the differential psychological benefits based on adolescents’ SI profiles. The article concludes by discussing implications for future research on Muslim adolescents’ successful adjustment.